2013
DOI: 10.1039/c3ee42516a
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen-doped graphene for dye-sensitized solar cells and the role of nitrogen states in triiodide reduction

Abstract: Nitrogen-doped graphene was demonstrated as an efficient and alternative metal-free electrocatalyst for dye-sensitized solar cells. Electrochemical measurements showed that the nitrogen-doping process can remarkably improve the catalytic activity of graphene toward triiodide reduction, lower the charge transfer resistance, and thus enhance the corresponding photovoltaic performance. Furthermore, the nitrogen doping levels ranging from 3.5 at% to 18 at%, as well as the nitrogen states (including pyrrolic, pyrid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
180
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 270 publications
(184 citation statements)
references
References 47 publications
4
180
0
Order By: Relevance
“…[103] Graphene aerogels 814 1.4 11.80 0.740 68 5.93 6.20 [21] Graphene nanosheets 383 39. 8 15.52 0.720 61 6.82 7.28 [60] Nitrogen-doped graphene - 35 10.50 0.729 71 5.40 5.10 [118] HNO 3 functionalized graphene -7.91 11.80 0.730 37 3.21 - [119] Single-walled carbon nanotubes -5 13.80 0.650 61 5.50 5.60 [105] Multi-wall carbon nanotube -0.82 16.20 0.740 64 7.67 7.83 [106] Aligned carbon nanotube --18.23 0.740 67 9.05 8.05 [107] Polyelectrolyte- [85] Hollow activated carbon nanofibers 1038 6.8 14.5 0.73 62 6.58 6.97 [115] MWCNT/MC nanofibers 562 12.3 14.9 0.76 56 6.35 6.31 [116] …”
Section: Carbon Nanofibermentioning
confidence: 99%
“…[103] Graphene aerogels 814 1.4 11.80 0.740 68 5.93 6.20 [21] Graphene nanosheets 383 39. 8 15.52 0.720 61 6.82 7.28 [60] Nitrogen-doped graphene - 35 10.50 0.729 71 5.40 5.10 [118] HNO 3 functionalized graphene -7.91 11.80 0.730 37 3.21 - [119] Single-walled carbon nanotubes -5 13.80 0.650 61 5.50 5.60 [105] Multi-wall carbon nanotube -0.82 16.20 0.740 64 7.67 7.83 [106] Aligned carbon nanotube --18.23 0.740 67 9.05 8.05 [107] Polyelectrolyte- [85] Hollow activated carbon nanofibers 1038 6.8 14.5 0.73 62 6.58 6.97 [115] MWCNT/MC nanofibers 562 12.3 14.9 0.76 56 6.35 6.31 [116] …”
Section: Carbon Nanofibermentioning
confidence: 99%
“…[ 41 ] Since the NGnP catalytic layer on FTO is more porous and thick compared to the Pt fi lm, it is diffi cult to discern whether the lower R CT of the NGnP5 cell stems from the intrinsically higher catalytic activity and/or from the higher electro-active surface area. Therefore, the relationship between the R CT and intrinsic catalytic activity and/or electroactive surface area can be described by Equation 2 and 3 , [ 42,43 ] J RT nFR…”
mentioning
confidence: 99%
“…Nitrogen-doped graphene was also used as a metal-free catalyst for DSSC. Hou et al [142] explored triiodide to iodide reduction using quite high levels of nitrogen doping in rGO (4-18 at%) and suggested that the nitrogen states affect the electrocatalytic activity more than the overall nitrogen content. Jeon et al [143] showed similar catalytic properties for edge-nitrogenated graphene multilayer nanoplatelets produced by dry ball-milling of natural graphite.…”
Section: Modification and Doping Of Graphene For Applications In Elecmentioning
confidence: 99%